2015
DOI: 10.1007/s10649-015-9607-1
|View full text |Cite
|
Sign up to set email alerts
|

The problem of assessing problem solving: can comparative judgement help?

Abstract: School mathematics examination papers are typically dominated by short, structured items that fail to assess sustained reasoning or problem solving. A contributory factor to this situation is the need for student work to be marked reliably by a large number of markers of varied experience and competence. We report a study that tested an alternative approach to assessment, called comparative judgement, which may represent a superior method for assessing open-ended questions that encourage a range of unpredictab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
1
42
0
2
Order By: Relevance
“…Although the latter were mentioned in almost half of the decision statements, this was almost always accompanied with a reflection on the complex aspects. Based on this study we can assume that comparative methods in particular are a valid method for the assessment of complex skills, as the comparative methods enable the teacher to obtain reliable scores for complex skills more easily than using analytic methods (Coertjens, Lesterhuis, Verhavert, Van Gasse, & De Maeyer, 2017;Jones & Inglis, 2015) and teachers focus on these higher order skills while assessing the texts. This also means that when rule-applying skills need to be assessed, other scoring methods such as rubrics or thick boxes might be more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the latter were mentioned in almost half of the decision statements, this was almost always accompanied with a reflection on the complex aspects. Based on this study we can assume that comparative methods in particular are a valid method for the assessment of complex skills, as the comparative methods enable the teacher to obtain reliable scores for complex skills more easily than using analytic methods (Coertjens, Lesterhuis, Verhavert, Van Gasse, & De Maeyer, 2017;Jones & Inglis, 2015) and teachers focus on these higher order skills while assessing the texts. This also means that when rule-applying skills need to be assessed, other scoring methods such as rubrics or thick boxes might be more suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers working in subjects other than mathematics need to consider carefully which population to draw judges from. For the case of mathematics we have previously found that educationalists, research students and research-active mathematicians all produce valid and reliable scores when judging students' work (Jones & Alcock, 2014;Jones & Inglis, 2015). However, an interesting case arose when CJ was applied to assess undergraduates' understanding of p values in the context of null-hypothesis significance testing (Bisson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Where no standardised measure is available then another option, albeit one that adds time and expense to a study, is to develop a rubric for the open-ended test and compare the marks with CJ outcomes for a sample of student responses. The rubric should be developed iteratively with reference to a sample of student responses, and the marking conducted by two independent experts on a second sample of responses (see Jones & Inglis, 2015). However, this option can only provide a comparison of two methods of assessing the same responses and so is merely a proxy for criterion validity.…”
Section: Criterion Validitymentioning
confidence: 99%
“…Since it was not assumed in the study that either proof would convey upon the student absolute conviction -Ba stable psychological feeling of indubitability about that claim^(p. 16), the focus was necessarily on students' relative conviction -which, in the context of this work, was defined as that which (from the students' perspective) provides a greater degree of conviction. 7 Third, as noted in Jones and Inglis's (2015) work on comparative judgments:…”
Section: On Using Comparative Task Methodologiesmentioning
confidence: 96%